1993
DOI: 10.1002/gps.930081008
|View full text |Cite
|
Sign up to set email alerts
|

Dementia, awareness and depression

Abstract: SUMMARYWe examined 170 outpatients, 103 with Alzheimer's disease, 43 with vascular dementia and 24 with various other causes, in order to investigate whether or not depressive symptoms were more likely to occur in dementia patients who had some degree of awareness of their cognitive deterioration. Awareness was rated on a four-point scale that assessed discrepancies between the patient's and the caregiver's history. The level of awareness was significantly related to the severity of dementia but not to depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
105
9
10

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 24 publications
11
105
9
10
Order By: Relevance
“…It was anxiety that appeared related to awareness, with the low awareness group reporting significantly less anxiety than the moderate awareness group. This is consistent with the findings of the majority of previous studies [14,16,49], although some did not find this association [50]. Some studies have reported an association with self-reported quality of life in dementia [6], but others have found no such association [7].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was anxiety that appeared related to awareness, with the low awareness group reporting significantly less anxiety than the moderate awareness group. This is consistent with the findings of the majority of previous studies [14,16,49], although some did not find this association [50]. Some studies have reported an association with self-reported quality of life in dementia [6], but others have found no such association [7].…”
Section: Discussionsupporting
confidence: 82%
“…The main methods of assessing awareness are general ratings of awareness based on interviews conducted by a clinician or researcher [16], calculation of discrepancies between patient and informant ratings on parallel questionnaires [17], and calculation of discrepancies between patient estimates of performance and actual task performance [18]. All have significant limitations [12,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The severity scores (range 1-3) of the observed individual neuropsychiatric symptoms were summed to generate a global score with a higher score for more severe behavioral symptoms. The degree of disease awareness was measured with the Guidelines for the Rating of Awareness Deficits (Verhey, Rozendaal, Ponds, & Jolles, 1993) in the Dutch cohort and according to the Reed anosognosia scale (Reed, Jagust, & Coulter, 1993) in the Nordic cohort. Both scales define awareness as the presence of explicit knowledge or recognition of own cognitive deficits according to a four-point scale.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Direct assessment of individuals' awareness about their condition and its implications is usually made on the basis of an interview (Verhey, et al, 1993). However, this approach is not without problems, not least how to interpret the responses given.…”
mentioning
confidence: 99%